치위생 분야의 감염관리 관련 국내 연구동향 분석: 주제범위 문헌고찰 - 양정아; Jeong-a Yang; 임순연; Soon-ryun Lim (Han'guk Ch'iwisaeng Hakhoe chi, 2023)
Objectives: This study analyzed a total of 30 domestic research trends related to dental infection control from 2013 to 2022. Methods: Two researchers analyzed the research question, “What are the research trends on infection control in dental hygiene at dental clinics and dental hygiene education institutions?” The selected literature was classified according to the research subject and the purpose of the study. Results: The study sample comprised 63% dental hygienists, 30% dental hygiene students, and 7% dental workers. The research topics on dental infection control were classified into knowledge, awareness, practice, infection control education, clinic environment, and infection control personnel. The largest proportion of research on dental infection control were about awareness and practice of infection control (69%). Clinic environment, knowledge, infection control education, and infection control personnel appeared in order. Conclusions: It is believed that this can be used as a reference material to present the direction of research design for researchers studying in infection control in the field of dental hygiene in the future.